Peningkatan Profesionalitas Guru Melalui Supervisi Akademik Kunjungan Kelas Model Coaching di SDN 1 Gondang Kabupaten Kendal - Susin, Muh. (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
The aim of the research is to increase teacher professionalism through academic supervision of coaching model class visits at SDN 1 Gondang, Limbangan District, Kendal Regency. This research is action research in accordance with the steps of the coaching model class visit supervision method carried out through two cycles, cycle 1 and cycle 2. The subjects of this research are teachers of grades 1 to grade six in science subjects. Data was collected by interviews, observation, documentation. Data analysis was done quantitatively for observation results and qualitative narrative for interview results. The results of this research on examining the RPP documents in accordance with National Education Ministerial Decree No. 41 of 2007, cycle 1 obtained an average of 71 and cycle 2 obtained an average score of 88 while in implementing learning in accordance with standards of success, cycle 1 obtained an average of 70 and in cycle 2 obtained an average of 87. This shows that there has been an increase in teacher professionalism after the supervision of class visits by the school principal. It is proven that through continuous academic supervision of class visits there is an increase in teacher professionalism in learning at SDN 1 Gondang accompanied by an increase in student learning outcomes. This research can contribute to thinking about the importance of the role of academic supervision of class visits in increasing teacher professionalism which has an impact on improving the quality of education.